PERANCANGAN PROGRAM LOYALITAS BAGI PENGUNJUNG DESTINASI WISATA DI KARESIDENAN KEDIRI - Martha Meisa; Indri Hapsari; Mochammad Arbi Hadiyat (CALYPTRA, 2018)
Kediri Residency have a lot of potential tourism place. Tourist’s visit to some place can influence their loyalty level. The indicator of their loyalty can be shown by revisiting the place and also give a recommendation to their relatives. The purpose of this research is to know how is the condition of tourism in Kediri Residency, to analyse the loyalty level of local tourism who have ever go to Kediri Residency, to know the indicator that influence loyalty, and to plan a program that can be increased loyalty level of the local tourism in Kediri Residency. This research is done using Structural Equation Modelling (SEM), to know what is the variable that influence loyalty. Then, quadrant analysist is done for variable that influence loyalty and can be improved. Quadrant analysist is used to group variables base on the importance level and the perception from tourism. The variables that have high importance level and low perception are the variables priority that must be improved. Quality Function Deployment (QFD) method is used to know the things that must be done by government and tourism manager to increase the loyalty level of local tourism.